Attitudes of mexican family doctors regarding the use of placebo in clinical practice - Gil Alfaro, Issa; Zavala Cruz, Gad Gamed; Rodríguez González, Azucena Maribel; Ramírez Aranda, José Manuel (2019)
The use of placebo has spread in clinical practice despite being controversial. In mexico the practice of family medicine is predominantty institutional and works with an essential medications list